Analisis Digitalisasi Sekolah Program Kelas Maya Berbasis Learning Management System (LMS) Model Hybrid Learning di SMA Negeri 18 Palembang - Eka Maryati Rahmi; Nur Ahyani; Mulyadi, Mulyadi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This research aims to analyze the implementation of a virtual classroom program based on a learning management system (LMS) with a hybrid class model at SMA Negeri 18 Palembang. The increasing need for digitalization in the field of education and efforts to answer the problems that occur at SMA Negeri 18 Palembang, namely the limitations of classes. This study explores how a learning management system can improve interaction and collaboration between teachers and students. The method used in this study is a qualitative approach where data is collected through interviews, observations, and documentation. The results of the study show that the implementation of school digitalization of the virtual classroom program based on the learning management system hybrid class model at SMA Negeri 18 Palembang in the planning aspect is in accordance with the main steps, namely identifying the needs of teachers and students, determining the right curriculum and conducting periodic evaluations of the implementation of the program. In terms of the implementation of the virtual classroom program based on the learning management system, the hybrid class model has been running well, but challenges have been found in terms of infrastructure, technology, and digital skills. In the evaluation aspect, the results were obtained that SMA Negeri 18 Palembang periodically evaluates the implementation of the program in order to obtain information about program improvements. This research provides input for further development in teacher training and the provision of adequate technological facilities, so that education digitalization can be effective.